1991
DOI: 10.1108/02689239110144415
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Autonomy and Work Satisfaction amongst Psychiatrists in the NHS

Abstract: Findings from a 1987 survey of work satisfaction among 193 consultants and junior doctors in psychiatry in Yorkshire are reported. While nearly two‐thirds of doctors report they are generally satisfied, a substantial number of consultants and junior doctors are dissatisfied with their resources, status and autonomy, and professional relationships. Regression analysis suggests that controlling for psychiatrists′ personal and professional characteristics and variables related to district management are important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Although professional autonomy may be conceived of as having several dimensions (Freidson 1970, Tolliday 1978, Schulz and Harrison 1986, Elston 1991), the dimensions that are central to these analyses concern the ability of individual physicians to determine their own clinical practices and to evaluate their own performance, in both cases without normally having to account to others. It is possible that autonomy relates positively to professional job satisfaction and ability to cope (see, for instance Schulz et al . 1991, Akre et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although professional autonomy may be conceived of as having several dimensions (Freidson 1970, Tolliday 1978, Schulz and Harrison 1986, Elston 1991), the dimensions that are central to these analyses concern the ability of individual physicians to determine their own clinical practices and to evaluate their own performance, in both cases without normally having to account to others. It is possible that autonomy relates positively to professional job satisfaction and ability to cope (see, for instance Schulz et al . 1991, Akre et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although professional autonomy may be conceived of as having several dimensions (Freidson 1970, Tolliday 1978, Schulz and Harrison 1986, Elston 1991, the dimensions that are central to these analyses concern the ability of individual physicians to determine their own clinical practices and to evaluate their own performance, in both cases without normally having to account to others. It is possible that autonomy relates positively to professional job satisfaction and ability to cope (see, for instance Schulz et al 1991, Akre et al 1997, Kapur et al 1999, but in the sociological literature, questions about autonomy lie at the heart of what it is to be a professional (Freidson 1970, Johnson 1972. This literature, however, manifests less agreement about how to conceptualise such challenges to autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…This article is derived from work conducted by some of the present authors in Germany and England [20,24]. This showed that peer review of cases by psychiatrists functioned to make visible the quality of care and helped to predict psychiatrist satisfaction and perceptions of clinical autonomy.…”
Section: Hypothesismentioning
confidence: 99%
“…There exists an official policy priority for the closure of long-stay psychiatric hospitals and their replacement by community care, in which both health care (the responsibility of the NHS) and social care (the responsibility of local government authorities) are integrated. While this policy seems largely to be supported by psychiatrists [24], there is a feeling among both health and social care workers that the available resources are inadequate [25]. Some of the Former Soviet Union Psychiatric care, along with most health services, was highly centralized and hierarchical within the former USSR [19].…”
Section: Englandmentioning
confidence: 99%
“…There is widespread academic agreement on the need to maintain a certain degree of autonomy for healthcare professionals in order to improve not only their ability to cope with everyday challenges, but also as a fundamental aspect of their personal performance and motivation (Harrison and Dowswell, 2002). The demands of autonomy and responsibility for the clinical units stem from those benefits that have been empirically demonstrated in the professional field (Schulz et al 1991, Akre et al 1997, Kapur et al 1999. The main focus of these analyses has been on the ability of professionals and clinical units to determine or establish their own clinical strategies and the assessment of their own performance.…”
Section: Autonomy and Responsibilitymentioning
confidence: 99%